Critical Discourse Analysis of U-20 World Cup Cancellation Polemic in Liputan6 Talks - Anugrah, Yuni Esa; Tutiasri, Ririn Puspita (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
Football is one of the most popular sports with the highest number of fans and enthusiasts among other sports. Issue about the cancellation of the U-20 World Cup in Indonesia has been widely reported by the media, both television and online media. This intersects with the status and rights of the official World Cup broadcaster obtained by EMTEK, which houses SCTV. The purpose of this research is to find out the discourse built and developed in the Liputan6 Talks episode "Di Balik Batalnya Piala Dunia U-20 dan Lobi Sakti Erick Thohir". This research is a descriptive qualitative research using the critical discourse analysis approach of Teun A. van Dijk model and data collection techniques through documentation, interviews, and literature studies. The analysis technique used in this research uses Vincent Moscow's theory of media political economy. The results of the analysis conducted by researchers regarding the discourse built and developed in the Liputan6 Talks news programme in this episode found that the discourse developed in the broadcast was a chronological story of the U-20 World Cup cancellation in Indonesia according to the government's version, especially PSSI.